Selfless love and human flourishing: a theological and a secular perspective in dialogue - Meszaros, J (2012)
The point of departure of this thesis is derived from a modern tendency to create a dichotomy between selfless love and human flourishing. Modern attempts to liberate the human being from heteronomous oppression and the moral norms promoting this have sometimes led to the conclusion that selfless love is harmful to human flourishing. Such a conclusion has gained momentum also through modernist re-conceptualisations of the self as an autonomous but empty consciousness which must guard itself against determination by the other. In effect, significant thinkers have replaced the notion of selfless love with a call for self-assertion over against the other, as key to the individual person’s well-being. This has been matched by Christian dismissals of the individual’s pursuit of human flourishing. In the face of modern insights into the ‘desirous’ nature of the human being, modern Christian theology has equally struggled to sustain the tension between the traditional Christian notion of selfless or self-giving love and human beings’ desire to affirm themselves and to find personal fulfilment in this world. Strands of Christian theology have, for instance, affirmed a self-surrendering love at the cost of dismissing the individual’s worldly desires entirely. In this thesis, I outline this situation in modern thought and its problematic consequences. With a view to discerning whether selfless love and human flourishing can be re-connected, I then undertake close studies of the theologian Paul Tillich’s and the moral philosopher and novelist Iris Murdoch’s conceptualisations of the self and of love. As I will argue, Tillich’s and Murdoch’s engagement with modern thought leads them to develop accounts of the self, which correspond with understandings of love as both selfless and conducive to human flourishing. On the basis of their thought I thus argue that selfless love and human flourishing can be understood as interdependent even today.